PENGARUH MODEL PEMBELAJARAN INKUIRI BERBASIS PROYEK TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK FASE E DI SMAN 1 PADANG - Fatira, Viona; Arsih, Fitri; Alberida, Heffi; Rahmatika, Helsa; Aulia Fikri, Refsya (Jurnal Biogenerasi, 2024)
Biology as part of science emphasizes learning that involves students directly through learning experiences that include science process skills. Based on the results of a preliminary study of the science process skills of phase E students at SMAN 1 Padang, it was obtained that the science process skills of students were still relatively low. This study aims to determine the effect of the project-based inquiry learning model on the science process skills of phase E students at SMAN 1 Padang. This type of research is a quasi-experimental study with a pretest-posttest control group design. The instrument used to measure students' science process skills is in the form of multiple choice questions. The sample class selected uses a purposive sampling technique. Data analysis using the paired sample test obtained significant results (0.000) <α value (0.05) so that it can be concluded that the project-based inquiry learning model has a positive effect on the science process skills of phase E students at SMAN 1 Padang.